Innovation in United Kingdom Teaching Methodology in the Digital Era - Dede Kurnia Putra; Amin Zaki (International Journal of Language and Ubiquitous Learning, 2024)
Background. Digital technology has had a significant impact on various sectors, including education. In the UK, many schools have started to adopt technology as an integral part of their teaching methods. However, there is still a gap in understanding the effectiveness and long-term impact of these technological innovations on student learning outcomes. Purpose. This study aims to explore and evaluate the impact of the use of technology in teaching in schools in the UK. The focus is on understanding how technology affects student learning outcomes, classroom participation, and teachers' readiness to integrate technology into the learning process. Method. The research approach used is mixed-methods, which combines quantitative and qualitative data. Quantitative data was obtained through questionnaires distributed to teachers and students in 30 schools in the UK, while qualitative data was collected through in-depth interviews with teachers to understand their experiences in using technology. Results. The results showed that schools that intensively adopted technology experienced an increase in student learning outcomes by 15%. Student participation is also increasing, especially in classrooms that use interactive digital tools. Teachers who have received special training show increased confidence in the use of technology. Conclusion. Technological innovations in teaching have proven to be effective in improving learning outcomes and student participation. However, there is still a gap in access to technology in rural areas that requires further attention.